Optimization Design and Performance of Small-Scale Downdraft Biomass Gasification: A Case Study For Air-Fresh Inlet - Homzah, Ozkar F.; Pratama, Rahmad Dandi; Sundari, Ella; Mardiana, Mardiana; Wilza, Romi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Biomass is the term for organic compounds, both animals and plants that can be reused as fuel or energy sources. Apart from that, gasification can be interpreted as a process of changing a solid fuel into a gas through thermochemical stages. The fuel used in the downdraft biomass gasification reactor is rice husks and coconut shells. The downdraft type biomass gasification reactor design used Autodesk Inventor professional software and for simulation using Ansys-R2 for 2021 student licensed. As the results after we create modified for inlet fresh-air showed the performance test of the hot start as flame temperature was increased to 21.7°C within the highest temperature reaches to 188.4°C. As a conclusion of modified performance test, we obtained the temperatures of pot-stove are slowly reaches from 6.38°C to 41.75°C of boiling water.